Intimacy and inequality: manumission and miscegenation in nineteenth-century Bahia (1830-1888) - Collins, Jane-Marie (2010)
This thesis proposes a new paradigm for understanding the historical roots of the myth of racial democracy in Brazil. In order to better comprehend the co-existence of race discrimination and racial democracy in Brazil it is argued that the myth itself needs to be subjected to an analysis which foregrounds the historically unequal relations of both race and gender. This study demonstrates how the enigma that is Brazilian race relations is the result of two major oversights in the scholarly work to date. First, the lack of critical attention to the historical processes and practices which gave rise to the so-called unique version of race relations in Brazil: manumission and miscegenation. Second, the sidelining of the role of gender and sex, as well as the specific and central place of black women’s labour, in theoretical formulations about Brazilian race relations.